Le préconscient traducteur - Kaës, René (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractFreudian psychoanalysis suggests the existence of a mechanism for interpreting and signifying the reactions of others. For the author, this is a type of translation activity occurring in the preconscious, which he examines from the viewpoint of intersubjectivity, that is, as a vehicle for creativity and interpretation. His analysis is based on experiments of group interdiscursivity and of crosscullural encounters.